2015
DOI: 10.1093/mnras/stv530
|View full text |Cite
|
Sign up to set email alerts
|

A large spectroscopic sample of L and T dwarfs from UKIDSS LAS: peculiar objects, binaries, and space density

Abstract: We present the spectroscopic analysis of a large sample of late-M, L, and T dwarfs from the United Kingdom Deep Infrared Sky Survey. Using the YJHK photometry from the Large Area Survey and the red-optical photometry from the Sloan Digital Sky Survey we selected a sample of 262 brown dwarf candidates and we have followed-up 196 of them using the echelle spectrograph X-shooter on the Very Large Telescope. The large wavelength coverage (0.30 − 2.48µm) and moderate resolution (R∼ 5000 − 9000) of X-shooter allowed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 101 publications
(107 reference statements)
7
43
2
Order By: Relevance
“…Using various assumptions for the initial mass function (IMF), birth rate, and cooling models (Burrows et al 1997; Baraffe et al 2003), the author confirms the relatively low number density of mid-L dwarfs, even for shallow IMFs. (2) Deacon & Hambly (2006) develop a similar calculation to model the present-day luminosity function (PDLF), which has been used to rule out extreme (halo-type) birth rates (Day-Jones et al 2013) and confirm the low space density of L/T transition dwarfs (Marocco et al 2015). The increasing number of late-T field dwarfs has been seen in several studies (e.g., Metchev et al 2008;Kirkpatrick et al 2012;Burningham et al 2013), which is seemingly a pile-up of cool dwarfs.…”
Section: Introductionmentioning
confidence: 84%
“…Using various assumptions for the initial mass function (IMF), birth rate, and cooling models (Burrows et al 1997; Baraffe et al 2003), the author confirms the relatively low number density of mid-L dwarfs, even for shallow IMFs. (2) Deacon & Hambly (2006) develop a similar calculation to model the present-day luminosity function (PDLF), which has been used to rule out extreme (halo-type) birth rates (Day-Jones et al 2013) and confirm the low space density of L/T transition dwarfs (Marocco et al 2015). The increasing number of late-T field dwarfs has been seen in several studies (e.g., Metchev et al 2008;Kirkpatrick et al 2012;Burningham et al 2013), which is seemingly a pile-up of cool dwarfs.…”
Section: Introductionmentioning
confidence: 84%
“…This approach has been widely used (see e.g. Marocco et al 2015;Manick et al 2015;Robertson & Mahadevan 2014, and references therein), with our methodology being similar to that used by Marocco et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…Our spectrum of 2MASS J02132062+3648506C, we classify this object as a T3 ± 0.5. Shown for comparison are the spectra for the young (∼100 Myr) T3.5 GU Psc b (Naud et al 2014), the young (∼300 Myr) T2.5 HN Peg B (Luhman et al 2007), the alternative T3 dwarf standard SDSSJ120602.51+281328.7 (Chiu et al 2006) [as suggested by Liu et al (2010)], the previous T3 standard 2MASS J120956.13−100400.8 (Burgasser et al 2004(Burgasser et al , 2006; now known to be a binary) and the blue T dwarf (Burningham et al 2010;Marocco et al 2015). All spectra are smoothed to similar resolutions and normalized to the J-band peak.…”
Section: Comparison With Evolutionary Modelsmentioning
confidence: 99%